Development of the E-Nabız Usage Behavior Scale: Validity and Reliability Study - Beyza Ünlü Büyükalim; Selma Pekgör; Fatih Yılmaz (Healthcare, 2026)
Objective: This study aims to evaluate the validity and reliability of the “e-Nabız Usage Behavior Scale” (eNUBS), developed to measure user behaviors toward Türkiye’s national personal health record system. Methods: This methodological study included 304 voluntary adult, non-healthcare participants at a hospital. Data were collected via an 8-item sociodemographic form and a 6-item draft scale. Construct validity was evaluated using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA); reliability was assessed using Cronbach’s alpha and item-total correlations. Results: Participants were 61.8% male, with a mean age of 37.79 ± 9.40. EFA confirmed a unidimensional structure, explaining 46.21% of the total variance. The Cronbach’s alpha was 0.72, and corrected item-total correlations ranged from 0.43 to 0.59. CFA demonstrated adequate model fit indices. Conclusions: The eNUBS is a brief, valid, and reliable tool for assessing real-world digital health portal usage, offering valuable guidance for digital health policy and for monitoring patient engagement.